2012
DOI: 10.1021/ie300821t
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of Gas–Liquid–Liquid Three-Phase Flow in an Annular Centrifugal Contactor

Abstract: A computational fluid dynamics (CFD) simulation of gas−liquid−liquid three-phase flow was carried out on an annular centrifugal contactor. An Euler−Euler, volume-of-fluid, multiphase-flow model was used for the three-phase flow simulation. The three-phase flow behaviors in the open and sealed inlet operation modes were investigated under various operating conditions. The location and morphology of the aqueous/organic interface were discussed in detail in light of the simulated pressure distribution. An interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…4(b)), the vortex is formed at the center of the rotor as well as in each separation cell. The numeric simulation results reported by Li et al (2012) are in an agreement with our observation. An explanation for this phenomenon should be raised from the aspect of the flow direction.…”
Section: Vector Fieldsupporting
confidence: 91%
See 1 more Smart Citation
“…4(b)), the vortex is formed at the center of the rotor as well as in each separation cell. The numeric simulation results reported by Li et al (2012) are in an agreement with our observation. An explanation for this phenomenon should be raised from the aspect of the flow direction.…”
Section: Vector Fieldsupporting
confidence: 91%
“…Recently, it was demonstrated that the flow field structure in the rotor region directly affects the separation efficiency of the ACC. With the assistance of the computational fluid dynamics (CFD) simulation, Li et al (2012) investigated the behavior of gas-liquid-liquid flow in the open and sealed inlet operational modes. The influences of various operational conditions including the rotation speeds, the phase ratios, and the flow velocities etc.…”
Section: Prefacementioning
confidence: 99%
“…The Reynolds stress model (RSM) was chosen as the turbulence flow model in this study because of its good performance in predicting a complex swirling flow. ,, The comparison of the results under different turbulence flow models with the experimental results is shown in the Supporting Information. The specific governing equations for both models could be found in published literatures. , …”
Section: Methodsmentioning
confidence: 99%
“…Using CINC V 02 geometry in [168], the two chambers were investigated in OpenFOAM , and, later, a hybrid multiphase solver was developed [169] with the goal to predict liquid-liquid interfacial area and droplet size distribution, thus mass transfer efficiency. Similar approach has been followed elsewhere using the dimensions of 70-mm INET ACC [170]. Authors in [171] introduced a technique that can be helpful to verify future CFD results, where non-invasive Computer Tomography was applied on a 3D-printed ACC.…”
Section: Hydrodynamic Studies On Annular Centrifugal Contactorsmentioning
confidence: 99%